Antigen-pulsed dendritic cells expressing macrophage-derived chemokine elicit Th2 responses and promote specific humoral immunity - Kikuchi, Toshiaki (American Society for Clinical Investigation, 2001)
Macrophage-derived chemokine (MDC) is a potent chemoattractant for antigen-specific T lymphocytes. We hypothesized that Adenovirus- (Ad-) transduced dendritic cells (DCs) overexpressing MDC would enhance the T cell–mediated humoral immune response specific for antigens presented by the DC. We challenged two strains of mice with lethal Pseudomonas aeruginosa infection 3 weeks after immunization with AdMDC-modified DCs pulsed with heat-killed P. aeruginosa. MDC-expressing DCs specifically attracted T lymphocytes and preserved typical DC surface phenotypes without growth factors in vitro. Mice immunized with AdMDC/Pseudomonas/DCs developed high levels of serum anti-Pseudomonas Ab’s and were protected from a lethal respiratory challenge with Pseudomonas. The in vivo protective immunity required CD4(+) T cells, B cells, and IL-4, but not CD8(+) T cells and IL-12. AdMDC/DCs pulsed with Pseudomonas yielded significant but not absolute cross-protection against different strains of P. aeruginosa. Pseudomonas-pulsed AdMDC/DCs protected mice from Pseudomonas but not Escherichia coli and vice versa; this microbe-specific protection correlated with microbe-specific induction of CD4(+) T cell proliferation and IL-4 secretion. Based on these observations, AdMDC-modified DCs pulsed with a killed bacteria may be a useful approach to vaccination against infectious disorders.